Performance of health laboratories in provision of HIV diagnostic and supportive services in selected districts of Tanzania. Issue 1 (December 2017) - Ishengoma, Deus; Kamugisha, Mathias; Rutta, Acleus; Kagaruki, Gibson; Kilale, Andrew; Kahwa, Amos; Kamugisha, Erasmus; Baraka, Vito; Mandara, Celine; Materu, Godlisten; Massaga, Julius; Magesa, Stephen; et al.
Abstract Background Roll-out and implementation of antiretroviral therapy (ART) necessitated many countries in Sub-Saharan Africa to strengthen their national health laboratory systems (NHLSs) to provide high quality HIV diagnostic and supportive services. This study was conducted to assess the performance of health laboratories in provision of HIV diagnostic and supportive services in eight districts (from four regions of Iringa, Mtwara, Tabora and Tanga), after nine years of implementation of HIV/AIDS care and treatment plan in Tanzania. Methods In this cross-sectional study, checklists and observations were utilized to collect information from health facilities (HFs) with care and treatment centres (CTCs) for HIV/AIDS patients; on availability of laboratories, CTCs, laboratory personnel, equipment and reagents. A checklist was also used to collect information on implementation of quality assurance (QA) systems at all levels of the NHLS in the study areas. Results The four regions had 354 HFs (13 hospitals, 41 Health Centres (HCs) and 300 dispensaries); whereby all hospitals had laboratories and 11 had CTCs while 97.5 and 61.0% of HCs had both laboratories and CTCs, respectively. Of the dispensaries, 36.0 and 15.0% had laboratories and CTCs (mainly in urban areas). Thirty nine HFs (12 hospitals, 21 HCs and six dispensaries) were assessed and 56.4% were located in urban areas. The assessed HFs had 199 laboratory staff of different cadres (laboratory assistants = 35.7%; technicians =32.7%; attendants = 22.6%; and others = 9.1%); with >61% of the staff and 72.3% of the technicians working in urban areas. All laboratories were using rapid diagnostic tests for HIV testing. Over 74% of the laboratories were performing internal quality control and 51.4% were participating in external QA programmes. Regional and district laboratories had all key equipment and harmonization was maintained for Fluorescence-Activated Cell Sorting (FACS) machines. Most of the biochemical (58.0%) and haematological analysers (74.1%) were available in urban areas. Although >81% of the equipment were functional with no mechanical faulty, 62.6% had not been serviced in the past three years. Conclusion Diagnostic and supportive services for HIV were available in most of the HCs and hospitals while few dispensaries were providing the services. Due to limitations such as shortage of staff, serving of equipment and participation in QA programmes, the NHLS should be strengthened to ensure adequate human resource, implementation of QA and sustainable preventive maintenance services of equipment.